www.immobilienbetrug.de - www.bankopfer.de - www.bankenkriminalität.de ... Grundvorgang und Folgen massenhaft betriebener Immobilienfinanzierung - Schanz, Günther (2001)
"This article deals with fraudulent sales of real estates to approximately 300.000 low and middle-income recipients. In all cases a common pattern was followed ("Treuhandmodell"). Within this model some German banks acted not only as lenders (of loans) but also, together with "trustees", as initiators. Sales people, often trained by banks, promised among other things investors/victims a bank-approved investment and, most importantly, a guaranteed rental income. A few years thereafter, following the collapse of the housing projects (Wohnanlagen), more and more people became unable to make further payments. – In at least 50 percent of all cases Bayerische Hypotheken- und Wechselbank (HypoBank) and – after the merger with Bayerische Vereinsbank – Bayerische Hypo- und Vereinsbank (HypoVereinsbank) is deeply involved in the fraud. How this financial institute deals with its responsibility for the economic damage and mental distress caused by its adventurous financing practices is not on